Updates in the Diagnosis of Intraductal Neoplasms of the Pancreas - Assarzadegan, Naziheh; Babaniamansour, Sepideh; Shi, Jiaqi (Frontiers in Physiology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest types of cancer worldwide. There are many reasons for this dismal prognosis, including the advanced stage at the time of diagnosis and the lack of effective therapeutic approaches. Intraductal papillary mucinous neoplasms (IPMNs) represent detectable and treatable precursor lesions of PDAC. Our understanding of the pathology of IPMNs has evolved over the past few decades, and new advances in diagnostic tools have emerged. The new World Health Organization (WHO) classification scheme now recognizes the previously considered variants of IPMNs, such as intraductal oncocytic papillary neoplasms (IOPNs) and intraductal tubulopapillary neoplasms (ITPNs), as distinct neoplasms. New imaging and molecular diagnostic tests are being developed to recognize these PDAC precursor lesions better. Here we review the advances in diagnostic tools for IPMNs, IOPNs, and ITPNs, emphasizing the new (5th edition, 2019) WHO classification for pathological diagnosis, molecular markers, new laboratory tests, and imaging tools.